Developing Family Resilience Models: Indicators and Dimensions in the Families of Pulmonary TB Patients in Surabaya - Dhian Satya Rachmawati; Nursalam Nursalam; Muhammad Amin; Rachmat Hargono (Universitas Airlangga, 2019)
Introduction: Family resilience is the process of adaptation and coping in the family as a functional unit. A lack of family involvement in the care programs for TB sufferers is one of the factors of concern. The purpose of this study was to analyze the indicators of the family resilience of patients with pulmonary TB.Methods: This study used an observational analytical method with a cross-sectional approach. The study population was the families of new pulmonary TB sufferers in the Surabaya area, taken using the rule of the thumb guideline with a sample of 130 respondents. The sampling technique using was systematic random sampling. The variables in this study were the stages of family resilience: survival, adaptation, acceptance, growing stronger and helping others, which were measured using a questionnaire. The data was analyzed using second CFA.Results: The results showed that the family resilience model is also the fit model. This refers to the results of the goodness of fit test. Family Resilience = 0.724 Survival, Family Resilience = 0.762 Adaptation, Family Resilience = 0.945 Acceptance, Family Resilience = 0.783 Growing Stronger and Family Resilience = 0.879 Helping Others.Conclusion: The results of this study provide information on the stages of family resilience and the ability of each stage so then it can be used as a reference when developing family nursing care plans for patients with pulmonary TB.